A Comparison of the SAO-Hipparcos reference frames - Arias, E. F. (2000)
The reference systems defined by the SAO and Hipparcos catalogues are compared using vector spherical harmonic analysis. The differences between astrometric data in both catalogues have been grouped into different data sets and separate harmonic analysis performed on them. The Fourier coefficients yield estimates of systematic errors in SAO catalogue.